Impact of Long Working Hours and Shift Work on Unmet Health Care Need Among Korean Workers - Hye-Eun Lee; Jeongbae Rhie (Elsevier, 2022)
Background: This study aimed to identify work-related risk factors, including long working hours and night/shift work, for unmet health care need using data of a representative panel of Korean adults. Methods: Associations between work-related factors and unmet health care need were analyzed using data of 3,440 participants (10,320 observations) from the 2011-2013 Korean Health Panel Study. A generalized estimating equation was used for the analysis of repeated measures. Results: The prevalence of unmet health care was 16.6%. After adjusting sex, age, socioeconomic status, work characteristics, and working more than 60 hours per week (odds ratio [OR]: 1.43, 95% confidence interval [CI]: 1.23-1.65) or 50-59 hours per week (OR: 1.26, 95% CI: 1.08-1.46) instead of 40-49 hours per week and night/shift work (OR: 1.27, 95% CI: 1.06-1.51) were associated with unmet health care need. Conclusion: Long working hours and night/shift work are risk factors for unmet health care need among the Korean working population.